206k views
15 votes
2x + 5y = 6

2x = 10 – 3y

Solve the simultaneous equations by substitution

(Sorry all my questions are maths i suck, more to come)

User Ravi Ram
by
4.7k points

1 Answer

5 votes

Explanation:

Given equations

2x + 5y = 6 .......i)

2x = 10 - 3y...... II)

Putting 2x = 10 - 3y in equation i

10 - 3y + 5y = 6

2y = 6 - 10

2y = - 4

y = - 4 / 2

y = - 2

Now putting y = - 2 in equation ii

2x = 10 - 3 * ( - 2)

2x = 10 + 6

2x = 16

x = 16 / 2

x = 8

So x = 8 and y = - 2

Hope it will help :)❤

User Rmeakins
by
5.1k points